PENGARUH DISIPLIN, KOMPETENSI DAN LINGKUNGAN KERJA TERHADAP KINERJA POLISI DI KEPOLISIAN RESOR TOBA SEKTOR BALIGE - Pandy Hasudungan Siahaan; Muhammad Alam Warda Ritonga; Rahmah Dewita; Hendra Paraduan Dongoran; Ari Pranata Surbakti (Universitas Islam Islam Sumatera Utara, 2021)
The problems of this research is how much influence dicipline to policy performance. How much influence competency to policy performance. How much influence work environment to policy performance. How much influence dicipline, competency, and work environment to policy performance. The purpose of this research is for know influence and analize of dicipline to policy performance. For know influence and analize of competency to policy performance. For know influence and analize of work environment to policy performance. For know influence dicipline, competency, and work environment to policy performance. The sample in this research is 33 policy, with data analysis technique used is multiple linear regression analysis. The research result dicipline effect positive and significanly to policy performance. Competency effect positive and significanly to policy performance. Work environment effect positive and significanly to policy performance. Dicipline, competency, and work environment effect positive and significanly to policy performance.